Legally Speaking Questioning a New Intellectual Property Right for Press Publishers: Considering the implications of the "link tax" provision of the proposed EU Directive for the Digital Single Market for traditional press publishers. - Samuelson, Pamela (Communications of the ACM, 2019)
The author comments on Article 11, or link tax, of the European Union's proposed Directive For the Digital Singe Market (DSM) that would provide press publishers an intellectual property right over online uses of their journalistic content. She covers the revenue advantages the measure would have for press publishers based on money earned from search engines and websites such as Google and Facebook.